PELATIHAN MEMBACA DAN MENULIS AL QUR’AN PADA ANAK ANAK DI MUSHOLA DARUSSALAM RT 01 RW 08 DESA DAWUAN KEC. TENGAH TANI DALAM MELANCARKAN MEMBACA DAN MENULIS AL QUR’AN - Andi Setiawan; Surakhman; Ria Permadi; Ajat Sudrajat (IAIC (Institut Agama Islam Cirebon), 2021)
In fact, there are 5 programs that we carry out in the Ahsar Koran, namely 1. Arabic Language Learning Service, 2. Calligraphy Service Activities, 3. Worship Practice Service Activities, 4. Children's Daily Prayer Service Activities, 5. Story Service Activities. Islamic. In all of these 5 activities, we got the results that children nowadays are easily bored or watched so that the obstacles for every teacher of the Koran in every prayer room must have a method of reciting it so that children always have interesting things, as we programmed in terms of ahsar reciting we make The interesting thing is that after the Koran is finished, they continue to be given learning together in Arabic, by playing with fun saying nouns in Arabic, and also the art of calligraphy so that children can write or color calligraphy. feel like writing calligraphy very enthusiastically follow it, and also we apply the practice of worship that can know the movement and reading of the prayer, in terms of Islamic stories so that children take stories in lessons about Islamic stories that can be practiced for daily activities